Declining HIV incidence in sub‐Saharan Africa: a systematic review and meta‐analysis of empiric data. Issue 10 (20th October 2021) - Joshi, Keya; Lessler, Justin; Olawore, Oluwasolape; Loevinsohn, Gideon; Bushey, Sophrena; Tobian, Aaron A R; Grabowski, M Kate
Abstract: Introduction: UNAIDS models suggest HIV incidence is declining in sub‐Saharan Africa. The objective of this study was to assess whether modelled trends are supported by empirical evidence. Methods: We conducted a systematic review and meta‐analysis of adult HIV incidence data from sub‐Saharan Africa by searching Embase, Scopus, PubMed and OVID databases and technical reports published between 1 January 2010 and 23 July 2019. We included prospective and cross‐sectional studies that directly measured incidence from blood samples. Incidence data were abstracted according to population risk group, geographic location, sex, intervention arm and calendar period. Weighted regression models were used to assess incidence trends across general population studies by sex. We also identified studies reporting greater than or equal to three incidence measurements since 2010 and assessed trends within them. Results: Total 291 studies, including 22 sub‐Saharan African countries, met inclusion criteria. Most studies were conducted in South Africa ( n = 102), Uganda ( n = 46) and Kenya ( n = 41); there were 26 countries with no published incidence data, most in western and central Africa. Data were most commonly derived from prospective observational studies ( n = 163; 56%) and from geographically defined populations with limited demographic or risk‐based enrolment criteria other than age (i.e., general population studies; n = 151; 52%). Across general population studies, average annual incidence declines since 2010 were 0.12/100 person‐years (95% CI: 0.06–0.18; p = 0.001) among men and 0.10/100 person‐years (95% CI: −0.02–0.22; p = 0.093) among women in eastern Africa, and 0.25/100 person‐years (95% CI: 0.17–034; p < 0.0001) among men and 0.42/100 person‐years (95% CI: 0.23–0.62; p = 0.0002) among women in southern Africa. In nine of 10 studies with multiple measurements, incidence declined over time, including in two studies of key populations. Across all population risk groups, the highest HIV incidence estimates were observed among men who have sex with men, with rates ranging from 1.0 to 15.4/100 person‐years. Within general population studies, incidence was typically higher in women than men with a median female‐to‐male incidence rate ratio of 1.47 (IQR: 1.11 to 1.83) with evidence of a growing sex disparity over time. Conclusions: Empirical incidence data show the rate of new HIV infections is declining in eastern and southern Africa. However, recent incidence data are non‐existent or very limited for many countries and key populations.